Breaking the metal ceiling: Female entrepreneurs who succeed in male-dominated sectors - Francisco Campos; Markus Goldstein; Laura McGorman; Ana Maria Munoz Boudet; Obert Pimhidzai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Occupational segregation significantly contributes to the earnings gender gap worldwide. We look at differences in outcomes for male and female enterprises and their sectors in Sub-Saharan Africa, a region of high female participation in entrepreneurship. Data on Uganda show that women breaking into male-dominated sectors make as much as men, and three times more than women staying in female-dominated sectors. Factors including entrepreneurial skill/abilities and credit/human capital constraints do not explain women's sectoral choices. However, information about profitability, male role models' influence, and exposure to the sector from family and friends are critical in helping women circumvent or overcome norms undergirding occupational segregation.
Keywords: J16; O17; O12; D22; D24; L25; L26; 330; gender; norms; labour market participation; entrepreneurship; small enterprises